A Scoping Review of Evidence-Informed Recommendations for Designing Inclusive Playgrounds - Brown, Denver M. Y.; Ross, Timothy; Leo, Jennifer; Buliung, Ron N.; Shirazipour, Celina H.; Latimer-Cheung, Amy E.; Arbour-Nicitopoulos, Kelly P. (Frontiers in Rehabilitation Sciences, 2021)
Background: Playgrounds provide children with many sensory, motor, and socioemotional experiences that are critical to child development. Unfortunately, playgrounds also represent an environment where children with disabilities experience barriers to accessing play. Structures and materials that are prominently found in almost all playground designs (e.g., swings, slides, sand) can present as obstacles for many children with disabilities to engage in independent play. Aims: This scoping review engaged in the empirical literature to address the research question, “What are the evidence-informed recommendations for designing inclusive playgrounds to enable participation for children with disabilities?” Consideration was given not only to the physical design of playgrounds, but also the playgrounds’ surrounding built and social environments. Methods: A systematic search of Medline, PsycINFO, CINAHL, EMBase, ERIC and Scopus was conducted. Only peer-reviewed literature published in English between January 1990 to January 2021, with a primary focus on inclusive playground structure design related to any type of disability were included. Data extraction included the study author(s), year of publication, country of origin, purpose, disability types considered, methods, sample characteristics and key findings. Key findings were synthesized into evidence-informed recommendations, which were later collated, using inductive content analysis, into five broader thematically congruent groups. Results: Thirty-five studies were included using case study (n = 17); observational (n = 6); survey (n = 6); experimental (n = 4); and multiple study (n = 3) designs. Thirteen evidence-based recommendations and one promising practice were categorized into five broad playground elements: entry points; surfacing and paths; features to foster inclusive play; staffing/supervision; and design process. Conclusion: These recommendations build upon previous design-based best-practices that focused exclusively on the physical design of the playground. Our recommendations have implications for how future playgrounds should be designed to maximize usability and inclusiveness and the overall playground experiences for children with disabilities.